Every utopia turns into dystopia. (December 2015) - Isaac, Rami K.
Abstract: This commentary reflects on the article written by the [authors] through discussing two points. First it will shed some light on the relationship between Utopia and Dystopia and taking the discussion in a slightly different direction that could strengthen their proposition in their article and second will clarify the aspect of emotion in the dark tourism experience. Highlights: New direction in integrating the notion of utopia and dystopia in the dark tourism phenomena. Clear presentation of the relationship between utopia and dystopia. Reflections on measuring emotional reaction in dark touism.